Reassessing The Translation of Anthropomorphic Verses in The Quran by N. J. Dawood: A Critical and Comparative Analysis - Mohamad, Mohd Zulfahmi; Sahad, Mohd Nizam (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
This study critically examines the translation of anthropomorphic verses in the Quran by N. J. Dawood, a Jewish Orientalist whose widely distributed English version, The Koran, has attracted attention for its theological implications. Grounded in the Islamic doctrine of tanzīh, which emphasises the absolute transcendence and incomparability of God, the study analyses 31 Quranic verses that contain anthropomorphic expressions. Through comparative textual analysis, Dawood’s interpretations are evaluated against those of two Muslim translators, namely, The Noble Quran by Muhammad Taqi al-Din al-Hilali and Muhsin Khan, representing the Salaf tradition, and The Quran: A New Translation by M. A. S. Abdel Haleem, which aligns with Ashʿarite theology. The findings reveal that Dawood’s renderings often lack theological consistency, with lexical substitutions, inconsistent capitalisation of divine references, and interpretive choices that introduce anthropomorphic imagery. In several instances, his translations are further influenced by Judeo-Christian narrative parallels, leading to doctrinal misrepresentations. The study argues that Dawood’s omission of classical Islamic sources such as tafsīr and ḥadīth literature results in theological distortions. It concludes that translations of Quranic verses involving divine attributes must be grounded in traditional Islamic hermeneutics to ensure linguistic integrity and preserve the foundational tenets of Islamic theology.